KATEGORI FATIS DALAM BAHASA MELAYU RIAU DIALEK KUOK - Hasnah Fauziah (LITERA, 2012)
This study aims to describe phatic categories of Riau Malay in the Kuok dialect, employing a descriptive method. The data were collected through interviews, note taking, and recording. The findings are as follows. First, the phatic forms consist of (a) particles, (b) words, (c) phrases, (d) phatic mixture, and (e) phatic combination. Second, the phatic functions include (a) breaking a conversation, (b) proving, (c) affirming, (d) emphasizing, (e) convincing, and (f) initiating and ending a conversation. Third, the phatic meanings include (a) emphasizing a request, (b) softening a satire, (c) emphasizing a refusal, (d) stating an intensity of a condition, (e) stating the quality of an action, and (f) emphasizing a denial.